The Uses of Mead in Habermas’ Social Theory. Before the Theory of Communication Action - Corchia, Luca (Italian Sociological Review, 2019)
The aim of this paper is to show how Habermas used the writings of George Herbert Mead. This subject has already been examined by the critical literature; however, the originality of this analysis with respect to previous studies lies in its philological approach. The result of the research proves that the interest of Habermas towards the American social psychologist originates well before the Theory of Communicative Action and accompanies the elaboration of Habermas’ research programme for over two decades. It is interesting to observe that the references to Mead’s writings continued to be very selective and focused on the same three particular areas: on the methodological level, around the problem of the foundation of the social sciences; on the theoretical level, around ontogenetic and phylogenetic development; on the moral level, around the justification of the discourse ethic and, more generally, the idea of a post-metaphysical concept of reason. This paper also shows the remarkable coherence with which Habermas is developing a general theory of society and a philosophy of rational discourse.